ANALISIS HUBUNGAN ANTAR MANUSIA (HUMAN RELATIONS) TERHADAP ETOS KERJA PADA PERUSAHAAN MANUFAKTUR DI MAKASSAR - Hendra Gunawan (Movere Journal, 2022)
This study aims to analyze the influence of human relations on work ethic inmanufacturing companies in the city of Makassar both partially and simultaneously. This research is an explanatory research using quantitative approaches and data collection techniques through questionnaires and observations. The total population in this study was 135 people with a sampling technique using simple random sampling where the number of populations was sampled regardless of the criteria of the entire population with a total sample of 135 people. Hypothesis testing using SPSS tools. The results showed that the relationship between people had a positive and significant effect on the work ethic of employees at the Manufacturing Company in Makassar City.